PENGARUH MODAL USAHA, LOKASI USAHA, DAN TEKNOLOGI INFORMASI TERHADAP PENDAPATAN UMKM DI KABUPATEN BANTUL - Andri Waskita Aji; Sela Putri Listyaningrum (Jurnal Ilmiah Akuntansi Indonesia, 2021)
Micro, Small and Medium Enterprises (UMKM), namely the activities of business actors that contribute significantly to the skills of producing raw goods into a product or service. The UMKM sector produces products that are needed by the community for daily needs, MSMEs are often faced with problems such as not maximizing the online market, lack of capital held for businesses, inefficient in managing finances. The purpose of this study is to examine the effect of business capital, business location and information technology on the income of MSMEs in Bantul Regency. The study used purposive sampling technique and data collection through questionnaires submitted to informants (MSME actors). The data review system uses multiple linear regression. This study provides evidence that the influence of business capital, business location and information technology has an important impact on the income of MSMEs, when the business capital owned is greater, then the more strategic the place of business is used to try and utilize information technology for a business, the bigger it will be. also the results of his business income. The results of this study, business capital, business location and information technology have a positive effect on the income of MSMEs. The conclusion in this study is that business capital has a positive effect on MSME income because with increased capital it will affect income because from increased capital business actors can add tools or goods sold, both business locations have a positive effect on MSME income because with a strategic location, With a large parking area and a place that is easily accessible, consumers will be interested in coming, and the last is information technology on MSME income, with the advancement of information technology, business actors can promote their goods on social media and sell their merchandise on digital platforms such as Go Food and Shopee. The income of business actors increases because they sell their goods online and can come directly at the shop.